5(3c-c)+3=43

Simple and best practice solution for 5(3c-c)+3=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3c-c)+3=43 equation:


Simplifying
5(3c + -1c) + 3 = 43

Combine like terms: 3c + -1c = 2c
5(2c) + 3 = 43

Remove parenthesis around (2c)
5 * 2c + 3 = 43

Multiply 5 * 2
10c + 3 = 43

Reorder the terms:
3 + 10c = 43

Solving
3 + 10c = 43

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 10c = 43 + -3

Combine like terms: 3 + -3 = 0
0 + 10c = 43 + -3
10c = 43 + -3

Combine like terms: 43 + -3 = 40
10c = 40

Divide each side by '10'.
c = 4

Simplifying
c = 4

See similar equations:

| (3x+2)(x+1)=4 | | 2w+9w+2w+8w+7w+w= | | 4a-2=7a-6 | | 6f+30=2f-8 | | 4(x+7.50)=40 | | 118-(3xb)= | | 4x-8=x+25 | | 49-2x=7x+16 | | 11-10x=103-38x | | 139-3x=6x+22 | | 2x+3(x-1)=27 | | 3(1+Y)=3-(5y+2) | | -17=-5+4u | | 2-6x=10-8x | | 4j-1+7= | | 15y=14(y+16) | | 3g+3(-5+4g)=1-g | | 2x^2-7x-16=-3x | | 3x+10=45-2x | | 3(6x-4)=22x | | 3(n-1)-2=4(n-4)-(n-11) | | 2(8q-1)+3(5q+6)= | | 12=2w+2 | | 10(x-5)=9(x+5) | | 9a-4+3a-33=23 | | 2(x-3)+4x=18 | | 5y-5=-35 | | 2(x-3)+4x=6.5 | | 7x-3x-8=24 | | 9y+y+8y+2y+5y= | | 2(x-3)=6.5 | | 3(2x-10)=6(x-10) |

Equations solver categories